Training Students’ Attitudes in Environmental Science Course Through Lesson Study - Rahmadiarti, Fida; Kuntjoro, Sunu; Budijastuti, Widowati (Jurnal Riset Biologi dan Aplikasinya, 2019)
The core competences of Environmental Sciences are to communicate and to understand the concepts of natural resources and environment, to solve related problems, and to have an environmental awareness. An effective effort is needed to train the environmental awareness. The purposes of this research were to evaluate how to train the attitudes of biology education study program students in the second semester who were taking the environment knowledge lecture. This research was quantitative and qualitative interpretation research by observing the learning process of Biology education students through lesson study. The research stages consisted of plan, do, and see in two cycles. The collected data included the results of observation on the learning process by the observer, the lecturers’ assessment related to the skills and attitudes during the learning process, and the students’ self-assessment on their attitudes. The data were analyzed descriptively. The research revealed that the students learned actively, they cooperated within groups, the class cleanliness was an indicator of attitude to environmental awareness because the lecturers always reminded the students related to the indicators of keeping the environment clean and treating garbage, the learning resources used challenged the students to work and discuss. The students’ attitudes towards environmental awareness are categorized as good-very good, the results of the lecturers’ assessment of the attitudes are categorized as good, and results of the students’ presentation skills are categorized as good-very good.